Decomposition and nutrient release patterns of Pueraria phaseoloides, Flemingia macrophylla dnd Chromolaena odorata leaf residues in tropical land use systems - Banful, B.; Ofori, K.; Kumaga, F.; Hauser, S.; Ndango, R. (2008)
The study determined the decomposition and nutrient release patterns of Pueraria phaseoloides, Flemingiamacrophylla and Chromolaena odorata leaf residues in young secondary forest and bush land use systems at Mfou, southern Cameroon. Residue mass loss after incubating fresh leaves for 120 days was C. odorata>P.phaseoloides > F. macrophylla. Mean weekly loss rates were 4.5, 3.9 and 2.8 per cent for C. odorata, P. phaseoloides and F. macrophylla, respectively. Across residue types, leaf mass loss was greater in the young secondary forest than in the bush land use. Soil texture and soil chemical properties were not correlated to leaf mass loss. Except for N, releases of P, K, Ca and Mg were of the order C. odorata≥ P. phaseoloides > F. macrophylla. Proportions of K released from the leafresidues were greater than those for the other nutrients.Half of the K was released within the first 7 weeks afterincubation for C. odorata and P. phaseoloides. Among the land uses, release of K in the forest was 1.8 times faster than in the bush. The slowest releases, irrespective of type of leaf residue, were in Ca and Mg. The study concluded that among the planted fallows, Puerariaphaseoloides had the greatest rate of nutrient release. It could, therefore, ensure greater nutrient availability to associated crops. The leaves of C. odorata are rich in all nutrients; hence, short-season crops could benefit from this source of nutrients if the weed is well managed.